Blow-Up Solutions for a Singular Nonlinear Hadamard Fractional Boundary Value Problem - Imed Bachar; Said Mesloub (Journal of Function Spaces)
We consider singular nonlinear Hadamard fractional boundary value problems. Using properties of Green’s function and a fixed point theorem, we show that the problem has positive solutions which blow up. Finally, some examples are provided to explain the applications of the results.